Employing Mind Maps to Foster Proactivity of Students Majoring in English in the Grammar Study - Nguyen Thi Huong, Lan (Papanda Publisher, 2025)
English grammar is a crucial and essential component in acquiring the English language. The acquisition of English grammar has emerged as a significant challenge for learners of all ages. This leads to the fact that identifying an effective approach to facilitate learners’ mastery of English grammar is material. Mind maps are deemed an appropriate option as they serve as a tool for articulating thoughts diversely, facilitating the effective utilization of both the left and right hemispheres of the brain to enhance activity and memory. As a result, mind maps have garnered heightened interest from educators. The study will examine the viewpoints of both instructors and students regarding the use of mind maps in the English grammar teaching and learning, grounded in the core aims and requirements of an innovative educational program. It is also designed to explore whether the implementation of mind maps in English grammar instruction can augment students’ engagement, promote learning efficacy, and foster learner autonomy, or if this approach constitutes an effective pedagogical method in teaching English grammar. To achieve the research goals, a quantitative method via a questionnaire is employed to assess stakeholders’ appraisal levels in educational activities. The findings indicate that both educators and learners greatly value the efficacy of utilizing mind maps in grammar instruction. Mind maps not only assist teachers in presenting lecture materials but also enable students to access and retain knowledge more effectively.